Conservation in post‐industrial cities: How does vacant land management and landscape configuration influence urban bees?. Issue 1 (10th October 2020) - Turo, Katherine J.; Spring, MaLisa R.; Sivakoff, Frances S.; Delgado de la flor, Yvan A.; Gardiner, Mary M.
Abstract: Rich pollinator assemblages are documented in some cities despite habitat fragmentation and degradation, suggesting that urban areas have potential as pollinator refuges. To inform urban bee conservation, we assessed local‐ and landscape‐scale drivers of bee community composition and foraging within vacant lots of Cleveland, Ohio, USA. Cleveland is a shrinking city, a type of urban area that has an over‐abundance of vacated greenspaces as a result of population loss and subsequent demolition of abandoned infrastructure. As such, Cleveland represents over 350 post‐industrial cities worldwide that are all promising locations for bee conservation. Across a network of 56 residential vacant lots (each 30 m × 12 m), we established seven unique habitats, including seeded native prairies, to investigate how vegetation management and landscape context at a 1, 500 m radius influenced urban bee communities. We assessed the distribution of several bee functional traits, diversity and abundance with pan and malaise traps. Foraging frequency was determined with plant–pollinator interaction networks derived from vacuum collections of bees at flowers. We observed higher bee richness and increased abundance of smaller sized bees as the size of surrounding greenspace patches increased within a 1, 500 m radius landscape buffer. Within habitats, seeded treatments had no effect on bees but greater plant biomass and shorter vegetation were correlated with increased bee richness and abundance. Plant–pollinator interaction networks were dominated by spontaneous non‐native vegetation, illustrating that this forage supports urban bees. Synthesis and applications . Our study indicates that proximity to larger greenspaces within an urban landscape promotes overall bee richness and increased occurrence of smaller bee species within residential vacant lots. While we did not observe our seeded native plants enhancing the bee community, native wildflowers were still establishing during the study and may have a greater influence when blooming at higher densities. Importantly, spontaneous non‐native vegetation provided the majority of urban bee's forage. Thus, vacant land that is minimally managed and vegetated with what many consider undesirable 'weeds' provides valuable habitat for bee conservation in cities. Abstract : Our study indicates that proximity to larger greenspaces within an urban landscape promotes overall bee richness and increased occurrence of smaller bee species within residential vacant lots. While we did not observe our seeded native plants enhancing the bee community, native wildflowers were still establishing during the study and may have a greater influence when blooming at higher densities. Importantly, spontaneous non‐native vegetation provided the majority of urban bee's forage. Thus, vacant land that is minimally managed and vegetated with what many consider undesirable 'weeds' provides valuable habitat for bee conservation in cities. Resumen: En algunas ciudades se documentan diversas comunidades de polinizadores a pesar de la fragmentación y degradación del hábitat, sugiriendo que las zonas urbanas tienen potencial como refugios de polinizadores. Para informar sobre la conservación de las abejas urbanas, evaluamos como es que las características del hábitat y del paisaje influencian a las comunidades de abejas en los lotes vacantes de Cleveland, Ohio, USA. Cleveland es una ciudad que tiene una sobreabundancia de áreas verdes desocupados como resultado de la perdida de habitantes y la posterior demolición de infraestructura abandonada. Como tal, Cleveland es una de las 350 ciudades postindustriales en todo el mundo, las cuales son prometedoras para la conservación de las abejas. A través de una red de 56 lotes residenciales vacantes (cada uno 30 × 12 m), establecimos siete tipos de hábitats, incluyendo praderas nativas, para investigar cómo el manejo de la vegetación y el contexto del paisaje en un radio de 1, 500 m influencian a las comunidades de abejas urbanas. Evaluamos la diversidad, abundancia, y la distribución de grupos funcionales de abejas usando trampas malaise y de plato. La frecuencia de búsqueda de alimento se determinó con redes de interacción planta‐polinizador derivadas de las recolecciones de abejas en flores usando aspiradoras de mano. Observamos una mayor riqueza y abundancia de abejas de menor tamaño a medida que el tamaño de los espacios verdes aumentaban dentro de un radio de 1, 500 m. Los tipos de hábitats no influenciaron a las abejas, sin embargo, una mayor biomasa vegetal y la vegetación corta estuvieron correlacionadas con una mayor riqueza y abundancia de abejas. Las redes de interacción entre plantas y polinizadores estuvieron dominadas por vegetación espontánea no nativa, ilustrando que este forraje beneficia a las abejas urbanas. Síntesis y aplicaciones . Nuestro estudio indica que la proximidad a espacios verdes grandes dentro de un paisaje urbano promueve la diversidad de abejas y aumenta la presencia de especies de abejas pequeñas dentro de los lotes vacantes. Si bien no observamos que la incorporación de plantas nativas beneficia a la comunidad de abejas, estas flores nativas aún se estaban estableciendo durante el estudio y podrían tener una mayor influencia al encontrarse en densidades más altas. Es importante destacar que la vegetación espontánea no nativa proporcionó la mayor parte del forraje de las abejas urbanas. Por lo tanto, los lotes vacíos con poco mantenimiento y con plantas consideradas como "malezas", son un hábitat importante para la conservación de las abejas en las ciudades.